2003
DOI: 10.1554/02-681
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the Pantropical Sea Urchin Tripneustes: Contrasting Patterns of Population Structure Between Oceans

Abstract: Abstract. To understand how allopatric speciation proceeds, we need information on barriers to gene flow, their antiquity, and their efficacy. For marine organisms with planktonic larvae, much of this information can only be obtained through the determination of divergence between populations. We evaluated the importance of ocean barriers by studying the mitochondrial DNA phylogeography of Tripneustes, a pantropical genus of shallow water sea urchin. A region of cytochrome oxidase I (COI) was sequenced in 187 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 64 publications
8
90
0
2
Order By: Relevance
“…Molecular phylogenies of regular echinoids (Lessios et al, 1999(Lessios et al, , 2001(Lessios et al, , 2003McCartney et al, 2000;Zigler and Lessios, 2004;Palumbi and Lessios, 2005) have agreed with Mayr's (1954) model of allopatric speciation. However, our data revealed that not all divergence highlighted in this study fits an allopatric model.…”
Section: Timing and Possible Causes Of Divergencementioning
confidence: 54%
See 1 more Smart Citation
“…Molecular phylogenies of regular echinoids (Lessios et al, 1999(Lessios et al, , 2001(Lessios et al, , 2003McCartney et al, 2000;Zigler and Lessios, 2004;Palumbi and Lessios, 2005) have agreed with Mayr's (1954) model of allopatric speciation. However, our data revealed that not all divergence highlighted in this study fits an allopatric model.…”
Section: Timing and Possible Causes Of Divergencementioning
confidence: 54%
“…However, one species of Mellita, M. grantii Mortensen, 1948, proved problematic for Mayr (1954) and he chose to ignore it in his analysis, stating that Mortensen (1948) had described M. grantii based on a single specimen from the midst of the range of M. longifissa Michelin, 1858. Mayr's (1954 model of allopatric speciation in echinoids has been supported by molecular phylogenies of regular sea urchins (Lessios et al, 1999(Lessios et al, , 2001(Lessios et al, , 2003(Lessios et al, , 2012McCartney et al, 2000;Zigler and Lessios, 2004;Palumbi and Lessios, 2005), but to-date this hypothesis has not been tested with a molecular phylogeny of a sand dollar genus.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding a well-documented biogeographic barrier dividing the tropical Indian and Pacific oceans, some studies suggest that certain species regularly exchange migrants between the two ocean basins (Lessios et al 2003;Klanten et al 2007). The results of our study add to the number of species that have genetically continuous populations between the tropical Indian and Pacific oceans.…”
Section: Geographic Population Structure and Gene Flowmentioning
confidence: 99%
“…Cold glacial periods followed by warm interglacial periods during the Quaternary caused interruptions and reconnections between water masses with important implications for the species distribution, evolutionary history and speciation processes (Wares and Cunningham 2001). For instance, the Pleistocene ice ages (after 2.4 my) subdivided and promoted population differentiation of a number of Atlantic and Pacific coastal species by periodically closing their migratory routes (Cunningham and Collins 1998;Lessios et al 2001Lessios et al , 2003.…”
Section: Introductionmentioning
confidence: 99%